Epidemiological Description of Arterial Hypotonia in Adolescents (In the Example of Fergana Region) - T.S., Nurmatova; N.S., Mamasoliev; R.R., Kurbonova; G.A., Usmanova; G.A., Usmanova (RA Journal of Applied Research, 2021)
The study analyzed data from a representative sample of 1,465 adolescents and young men involved in a one-stage epidemiological study. The prevalence of arterial hypotonia (AG) was 18.6% (10.8% among adolescents and 45.2% among boys; P <0.001). The identified results should be taken into account in the development and implementation of prevention programs for adolescents and adolescents living in the regions of Uzbekistan.